CT AND ANGIOGRAPHY OF ESTHESIONEUROBLASTOMA - PEKANAN, Patchrin; PONGPECH, Sirintara; VORRASUBIN, Wara; PRACHASILPCHAI, Pravit; TANTIWIWAT, Chitchanok (The ASEAN Journal of Radiology, 2023)
A case report of Esthesioneuroblastoma in a 39-year-old female patient was presented. The mass was a slow growing one, when found it was quite extensive to be located in both nasal cavities, medial part of right maxillary sinus, both ethmoid sinuses, left sphenoid sinus, left orbital cavity, and epidural space of the anterior cranial fossa. Bowing pattern, bony erosion and tumoral calcification was shown by CT scan. The metastatic tumor to right parotid gland was already present. The tumor received blood supply from both maxillary arteries and left ophthalmic artery and the main feeder was left maxillary artery which indicated that the tumor originated from the left side of the nasal cavity.